STUDI KOMPARASI KINERJA SAHAM UNGGUL DAN SAHAM LIKUID SEBELUM DAN SAAT PANDEMI - Jayanti, Dwi Nur; Manzilati, Asfi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The pandemic Covid-19 is a pandemic that attacks public health so that it has an impact on the economy, especially the capital market. The pandemic Covid-19 resulted in a weakening of the IHSG by up to 26.96%, apart from the weakening of the IHSG there were superior and liquid stocks which were the stocks most in demand by investors because they had the best performance and had a high probability of providing high profits. The purpose of this research is to compare the performance of superior stocks and liquid stocks before and during the pandemic by using stock returns, transaction volume and stock risk. By using the Wilcoxon rank test method. The results of this study indicate that stock performance through stock returns on superior stocks does not have a significant effect and there is a decrease during a pandemicc, while liquid stock returns also do not have a significant effect but there is a slight increase during a pandemic, the transaction volume of superior stocks and liquid stocks has a significant effect and occurs an increase in transaction volume during a pandemic, the risk of superior stocks and liquid stocks also has a significant influence and there is an increase in risk during a pandemic.